APLASTIC ANEMIA - Ni Made Dharma Laksmi; Sianny Herawati; Wayan Putu Sutirta Yasa (E-Jurnal Medika Udayana, 2013)
Aplastic Anemia describes a disorder of the clinical syndrome is marked by a deficiency of red blood cells, neutrophils, monocytes and platelets in the absence of other forms of bone marrow damage. Aplastic anemia is classified as a rare disease in developed countries the incidence of 3-6 cases / 1 million inhabitants / year. The exact cause of someone suffering from aplastic anemia also can not be established with certainty, but there are several sources of potential risk factors. Prognosis or course of the disease varies widely aplastic anemia, but without treatment generally gives a poor prognosis